SURVEILLANCE OF EMERGING AND RE-EMERGING DISEASES: CHALLENGES FOR GLOBAL HEALTH AND MULTIPROFESSIONAL ACTION - Brilhante, Vânia Cristina Ribeiro; de Oliveira, Dayvison Santos; Rebelo, Rita de Cássia Maia; de Sales, Mariana Elizabeth Lopes; Facioni, Jeane da Silva; Araujo, Tchescolly Dias; da Fonseca, Micheline Santos; de Morais Filho, Valdemar Mendes; Araújo, Juliana Botelho; Silva, Michelle Barbosa; Cruz, Débora Teruko Kajitani; Carretilha, Arilana de Jesus; et al. (Seven Editora, 2026)
The surveillance of emerging and reemerging diseases has become a key strategy for protecting global health in a context shaped by environmental, social, and epidemiological transformations. This study aimed to analyze the challenges related to disease surveillance and to discuss the importance of multiprofessional practice in developing effective responses. This is a qualitative study conducted through an integrative literature review, based on recent scientific evidence from international databases. The findings indicate that environmental changes, increased human–animal interaction, population mobility, and weaknesses in health systems have contributed to the rise of emerging and reemerging diseases. The epidemiological profile has become more complex, with the coexistence of multiple infectious agents and the growing threat of antimicrobial resistance. In this context, epidemiological surveillance faces challenges related to data integration, technological use, and structural inequalities across countries. The role of multiprofessional teams is highlighted as essential for early detection, clinical management, and implementation of preventive strategies. It is concluded that strengthening health surveillance, combined with interdisciplinary collaboration and international cooperation, is crucial to address current and future challenges, ensuring global health security.